Unsteady Hydromagnetic Flow of a Heat Absorbing Dusty Fluid Past a Permeable Vertical Plate with Ramped Temperature - m Das; b.k Mahatha; Raj Nandkeolyar; b.k Mandal; k Saurabh (Journal of Applied Fluid Mechanics, 2014)
The unsteady flow and heat transfer of a viscous incompressible, electrically conducting dusty fluid past vertical plate under the influence of a transverse magnetic field is studied with a view to examine the combined effects of suction, heat absorption and ramped wall temperature. The temperature of the wall is assumed to have a temporarily ramped profile which goes on increasing up to a certain time limit and then becomes constant. To investigate the effect of rampedness in wall temperature, the solution for the flow past an isothermal wall is also obtained. The governing partial differential equations are solved using Laplace transformation technique in which the inversion is obtained numerically using Matlab. To validate the results of numerical inversion a comparison between the numerical and analytical values of fluid and particle temperatures and Nusselt number is also presented. The effects of pertinent flow parameters affecting the flow and heat transfer are investigated with the help of graphs and tables. It is found that the increase in suction, heat absorption and particle concentration contribute in thinning the thermal and momentum boundary layers and the velocity and temperature for both the fluid and particle phases are higher in the case of a flow past an isothermal plate than that of a flow past a plate with ramped temperature.